Gestión del capital intelectual en carreras de ingeniería para el desarrollo tecnológico en la industria peruana Intellectual capital - Ormachea Freyre, Fernando (2019)
This article presents a proposal for redesigning the management of internships by integrating academic and research units, with teachers and students interacting in applied research under the scheme of planned communities of practice, supported by information and communication technologies to facilitate direct or remote communication, capture, processing and consolidation of dispersed knowledge, generating intellectual capital useful for the benefit of businesses and careers involved.